No-tillage with straw mulching promotes the utilization of soil nitrogen by rice under wheat–rice and oilseed rape–rice cropping systems - Yan, Fengjun; Zhou, Wei; Sun, Yongjian; Guo, Changchun; Xiang, Kaihong; Li, Na; Yang, Zhiyuan; Wu, Yunxia; Zhang, Qiao; Sun, Yuanyuan; Wang, Xiyao; Ma, Jun (Frontiers in Plant Science, 2023)
Introduction To investigate the effects of no-tillage with straw mulching on the absorption and utilization of soil nitrogen (N), fertilizer N, and straw N by rice under paddy-upland rotations. Methods A field experiment with three cropping systems: fallow–rice rotation without straw mulching (FRN), wheat–rice rotation with wheat mulching in rice season (WRS), and oilseed rape–rice rotation with oilseed rape straw mulching in rice season (ORS) was conducted from 2015 to 2017, along with a mini-plot experiment with 15N-labeled urea and straws, which was conducted in 2017. Results No-tillage with straw reduced rice N uptake up to 20 days after transplanting, the total amount of fertilizer N uptake of WRS and ORS rice plants was 46.33 and 61.67 kg/ha, respectively, which was 9.02 and 45.10% higher than that of FRN plants. Soil N was the main source for rice growth, followed by fertilizer N. Soil N uptake by WRS and ORS rice plants was 21.75 and 26.82% higher than that of FRN plants, accounting for 72.37 and 65.47%, respectively, of the total N accumulated in rice plants. Straw mulching increased the N utilization efficiency of tillering, panicle, and total fertilizer by 2.84–25.30%; however, base fertilizer was dependent on straw mulching. The total amount of N released from WRS and ORS straw mulching in the rice season was 34.97 and 24.82 kg/ha, respectively; however, only 3.04 and 4.82% of it was absorbed by the rice plants, accounting for only 0.62 and 0.66% of the total accumulated N. Discussion No-tillage with straw mulching under paddy-upland rotations increased the N utilization of rice, especially for the absorption of soil N. These results provide theoretical information for the effective utilization of straw and rational N application practices in rice-based cropping systems.